The Mediating Effect of Academic Stress on Fear of Failure and Academic Procrastination of College Students - Obenza, Brandon Nacua; Kileste, Fer Livette; Mesajon, Joemelyn; Canciller, Cristamae; Escudero, Mari Janzyle Faith; Ligasan, Nina Grace; Palacios, Gretchen; Solis, Jamila (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
This quantitative non-experimental study delves into the factors associated with academic procrastination among college students. Using stratified random sampling, the identified and included 409 students from different higher educational institutions in Region XI, Philippines. The study adopted validated measurement scales for the Academic Procrastination, Academic Stress, and Fear of Failure. Using SmartPLS 4.0 software a mediation analysis was conducted on the data. The results revealed that college students manifest moderate levels of academic stress, fear of failure, and academic procrastination. Further, significant direct and indirect effects were found to all hypothesized paths thus supporting the hypothesized mediation model of academic procrastination. The coefficient of determination (R² = 0.433) indicates that fear of failure and academic stress together explain 43.3% of the variance in academic procrastination among college students. Implications and limitations of the study were also provided.